An econometric analysis of female director on company performance the non linear effects - Chen, Ming (2012)
The aim of this paper is to investigate an econometric analysis of nonlinear effects of gender composition of the board of directors on company performance using Malaysian initial public offering (IPO) companies. It also examines other factors of board composition which are independent directors and non-executive director. This study finds that gender diversity on board does not affect the company financial performance based on return on assets, return on equity and Tobin's Q using a sample of 123 IPO companies from the total population of 230 IPO companies which were listed during the period of 2005 to 2012. Results reveal that there is no significant relationship between the percentage of independent and non-executive directors on board and company financial performance, either linearly or nonlinearly, except at upper 80th percentiles of return on equity, this study covers strong evidence that more female directors on board are associated with significantly high return. This research contributes to the existing literature on gender especially in the context of IPO companies using econometric analysis. This is one of the rare comprehensive study uses multiple statistics tools to examine the factors of board composition using recent Malaysian IPOs data